Biomimetic Hierarchical Superstructures: Approaches Using Bicontinuous Microemulsions and Electrodeposition - Siller-Martínez, Ana Sofia; Fuentes, Keyla M.; Adesuji, Elijah T.; Aceves, Frida; Torres-Guerrero, Verónica O.; Guardado-Villegas, Esther; Basilio-Bernabé, Karla; Ceballos, Manuel; Navarro-Segura, María; Rivera-Rangel, Rubén Darío; Arizpe-Zapata, J. Alejandro; Videa, Marcelo; et al. (Frontiers in Materials, 2022)
The current challenges in developing novel nanotechnological processes have led us to explore new methods for synthesizing nanomaterials whose functionalities rely on their structural complexity. In this respect, Nature has always been a source of inspiration for proposing innovative technologies to improve the quality of life. Hierarchical superstructures (HSS) are of great interest because the self-assembly of low-dimensional nanostructures (up to the macroscale) allows the control and optimization of performance by coupling the properties of the individual blocks. Self-assembled surfactant structures are convenient for HSS synthesis because they provide a confined reaction medium which confers excellent control over the size of the building blocks. Furthermore, bicontinuous microemulsions offer a soft three-dimensional template due to their interconnected nature. Similarly, electrodeposition routes offer fast, robust, clean, and reproducible ways to synthesize metallic and multimetallic HSS. The combination of soft-templating and electrodeposition is a powerful tool for controlling the morphology and composition of the material. This work reviews polymeric, ceramic, and metallic hierarchical superstructures synthesized using bicontinuous microemulsions and electrodeposition techniques and compares them with matching natural patterns. The aim is to show how these synthetic routes can be exploited to obtain efficient biomimetic nanomaterials that improve their properties.